Children's nutritional profile from a school in Belém, PA, Brazil - Ferreira dos Santos, Larissa do Socorro; Martins e Silva, Sheila Cristina; Leal Soares Ramos, Edson Marcos (Journal of Health Care, 2017)
Introduction: In Brazil, several changes in the nutritional profile of the population have occurred, which affect not only the adult population, but also children and adolescents, with an increase in the overweight and obesity rates at increasingly early ages. Objective: The present study aimed at tracing the nutritional profile of children in preschool age, enrolled at the Jesus Early Childhood Education School, located in the city of Belém/PA. Methodology: The methodology is about a cross-sectional research conducted with children from3 to 6 years old, of both genders, from November 2015 to August 2016. Measurements of weight, stature, age and body mass index (BMI) were collected from these children. Afterwards, anthropometric indexes BMI/Age (BMI/A) and Weight/Stature (W/S) were calculated inz-score, according to 2006/2007 WHO, in order to determine the nutritional diagnosis. Results: The evaluation was made with 76 children, being 40 (52.63%) of the male sex and 36 (47.36%) of the female sex. From the total of evaluated children, 67 (88.15%) demonstrated adequate nutritional diagnosis, 3 (3.94%) deficit and 6 (7.89%) excess. Conclusion: It was concluded that the majority of children had a eutrophic diagnosis, given that they have nutritional and psychological counseling, as well as a balanced diet from the school in which they study, a fact that contributes to an adequate nutritional status.
Keywords: Nutritional Status; Child Health; Preschool; Anthropometry